WO3 / CN composite photocatalytic material based on in-situ coupling and preparation method thereof
By growing WO3 nanorods in situ on CN nanosheets, forming WO3/CN composite photocatalytic materials, the problems of low utilization rate of existing photocatalytic materials in the visible light region and high recombination rate of photogenerated electron-hole pairs are solved, and high efficiency is achieved photocatalytic properties and activities.
Patent Information
- Application Number
- CN202411722017.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a WO3 / CN composite photocatalytic material based on in-situ coupling, and also relates to a method for preparing the WO3 / CN composite photocatalytic material. Background Art
[0002] Green photocatalytic technology has received extensive attention in applications related to environmental remediation and sustainable development. Traditional photocatalytic materials such as TiO2 have strong oxidizing ability, but their utilization rate in the visible light region is low, which limits their application in environmental pollution control. In recent years, graphite phase carbon nitride (CN) has attracted much attention due to its good stability and visible light response characteristics. However, due to the high recombination rate of photogenerated carriers and small specific surface area of CN materials, their photocatalytic activity is limited. WO3 (tungsten trioxide), as a wide-bandgap photocatalytic material, has excellent visible light response ability, but its rapid recombination of photogenerated electron-hole pairs also hinders its widespread application in the field of photocatalysis. Summary of the invention
[0003] Purpose of the invention: The purpose of the present invention is to provide a WO3 / CN composite photocatalytic material; another purpose of the present invention is to provide a method for preparing the above-mentioned WO3 / CN composite photocatalytic material, which obtains a composite photocatalytic material with a specific morphology through a specific process. The composite photocatalytic material has a large specific surface area and multiple active sites, and can achieve better adsorption of reactants, thereby greatly improving the photocatalytic performance of the photocatalytic material.
[0004] Technical solution: The WO3 / CN composite photocatalytic material of the present invention comprises CN nanosheets and WO3 nanorods in situ grown on the CN nanosheets.
[0005] The preparation method of the WO3 / CN composite photocatalytic material comprises the following steps:
[0006] (1) dispersing thiourea in an ethanol solvent to obtain a thiourea solution; then adding WCl6 thereto, and continuously stirring at room temperature to mix the materials uniformly;
[0007] (2) subjecting the mixed material of step (1) to ultrasonic treatment to form a uniform suspension; the low surface tension of ethanol causes the solid to settle at the bottom of the beaker, and after solid-liquid separation, the obtained solid is dried;
[0008] (3) After drying, calcination is performed to obtain a WO3 / CN composite photocatalytic material.
[0009] Wherein, in step (1), the solvent is ethanol with a volume fraction of 95%.
[0010] Wherein, in step (1), the mass ratio of WCl6 to thiourea added is 10:0.1-0.5.
[0011] Wherein, in step (1), the concentration of thiourea in the thiourea solution is 50-60 g / L.
[0012] Wherein, in step (2), the ultrasonic treatment time is not less than 0.5h.
[0013] Wherein, in step (2), the drying temperature is 60-70° C. and the drying time is 6-8 hours.
[0014] Wherein, in step (3), the calcination temperature is 500-550°C, the calcination time is 2.5-3h, and the heating rate is 2-10°C / min.
[0015] Wherein, in step (3), after calcination, the mixture is naturally cooled to room temperature, then washed with anhydrous ethanol and distilled water, and then dried at 60-70°C.
[0016] The present invention combines CN and WO3 to form a heterojunction through a simple chemical deposition process, which can effectively inhibit the recombination of photogenerated electron-hole pairs, thereby improving the photocatalytic efficiency of the photocatalytic material by promoting the separation of photogenerated electron-hole pairs; at the same time, the interaction between CN and WCl6 can form loose needle-shaped WO3 nanorods on CN nanosheets at high temperature. This heterostructure has a large specific surface area and can expose more active sites, which not only utilizes better adsorption reactants, but also effectively improves the charge transfer and separation between CN and WO3, thereby effectively improving the photocatalytic activity of the composite photocatalytic material.
[0017] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The WO3 nanorods of the present invention grow on the CN nanosheets, which increases the specific surface area and porosity of the material, and helps to improve the reaction activity of the photocatalytic material; the specific surface area of the CN-0.3 sample prepared by the present invention is about 15 times and 13 times higher than that of pure CN and WO3, respectively, thereby providing more reaction active sites; (2) Secondly, the coupling of WO3 and CN can expand the visible light absorption range of the composite photocatalytic material. The absorption band edge of the CN-0.3 prepared by the present invention is red-shifted to 521 nm, which increases the material's responsiveness to light; (3) Again, the oxygen vacancies between CN and WO3 promote the transfer of photogenerated electrons, reduce the recombination of electron-hole pairs, and improve the photocatalytic activity; the PL spectrum shows that with the increase of WO3 loading, the recombination rate of photogenerated electron-hole pairs is greatly reduced, and the CN-0.3 prepared by the present invention exhibits good electron separation efficiency; (4) Finally, the conduction band and valence band of WO3 match well with CN, forming an efficient electron-hole separation structure, which can significantly improve the photoreduction and photooxidation capabilities of the composite photocatalytic material. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 SEM images of CN, WO3 and CN-X; (a) CN-0.3; (b) CN; (c) WO3; (d) CN-0.1; (e) CN-0.2; (f) CN-0.5;
[0019] Figure 2 X-ray diffraction (XRD) patterns of CN, WO3 and CN-X (Examples 1 to 4);
[0020] Figure 3 The rate diagram of degradation of organic matter rhodamine (RhB) by CN, WO3 and CN-X (Examples 1 to 4);
[0021] Figure 4 The graph is a comparison of the photocatalytic hydrogen production rates of CN, WO3 and CN-X (Examples 1 to 4) under visible light;
[0022] Figure 5 This is a comparison chart of hydrogen production efficiency of the CN-0.3 sample cycle test prepared in Example 1;
[0023] Figure 6 The photocatalytic hydrogen production rate diagram of the composite photocatalytic materials prepared in Example 1 and Examples 5, 6, 7, and 8 under light irradiation;
[0024] Figure 7 This is a comparison chart of the photocatalytic hydrogen production rates of the photocatalytic materials prepared in Example 1 and Comparative Examples 1, 2, 3, and 4 under light irradiation;
[0025] Figure 8 It is a process flow chart of the method of the present invention and a mechanism diagram of the prepared composite photocatalytic material in photocatalytic hydrogen production; wherein (a), (b), and (c) are HR-TEM images of CN-0.3 at different sizes, respectively; (d) is a high-resolution transmission lattice fringe image of the CN-0.3 sample. DETAILED DESCRIPTION
[0026] Example 1
[0027] The preparation method of the WO3 / CN composite photocatalytic material of the present invention comprises the following steps:
[0028] (1) Add 10.0 g of thiourea to 20 mL of anhydrous ethanol and stir at room temperature. Then weigh 0.3 g of WCl6 and add it to the thiourea solution. Continue stirring at room temperature to fully mix the reaction materials.
[0029] (2) placing the mixed solution of step (1) in an ultrasonic instrument for ultrasonic treatment for 0.5 hours to form a uniform suspension; the low surface tension of ethanol causes the solid to settle at the bottom of the beaker, taking out the solid mixture at the bottom and placing it in a 60° C. oven for drying for 6 hours;
[0030] (3) Grind the solid mixture obtained in step (2) into powder and put it into a 50 mL crucible; then, heat the mixture to 520° C. at a heating rate of 5° C. / min in a resistance furnace and calcine for 3 hours; after calcination, cool the mixture naturally to room temperature; wash the powder with anhydrous ethanol and distilled water, and then dry it at 60° C. to obtain an in-situ coupled heterogeneous photocatalytic material of nitrogen-containing carbon and tungsten trioxide, which is recorded as CN-0.3.
[0031] pass Figures 1-2 , namely, X-ray diffraction (XRD) and scanning electron microscopy (SEM) were used to characterize the structure of the photocatalytic material CN-0.3, confirming that WO3 nanorods grew uniformly on CN nanosheets.
[0032] pass Figures 1-2 By comparison, the CN sample is an irregular block structure with a significantly loose surface, while the WO3 sample is a block with a smooth surface. Compared with CN-0.1, CN-0.2, and CN-0.5, the CN-0.3 sample has pine needle-like WO3 nanorods with a distinct structure, which grow together with the layered CN and aggregate more closely. This structure is conducive to increasing the contact area between WO3 and CN, thereby increasing the reactive sites.
[0033] The photocatalytic material CN-0.3 prepared in Example 1 showed significant activity in the photocatalytic hydrogen production experiment under visible light. In the photocatalytic hydrogen production experiment, a 300W xenon lamp (λ>420nm, CEL-HXF300) was used to simulate natural light to carry out the photocatalytic hydrogen production experiment. 0.4mL of 3% H2PtCl6 solution (Pt precious metal catalytic material) was added to a mixed solution consisting of 40mL deionized water and 10mL triethanolamine, and then 20mg of the photocatalytic material CN-0.3 was placed therein, and it was evenly dispersed by ultrasound and stirring; a vacuum pump was used to remove all gases in the reaction system until the reaction system was under negative pressure; on this basis, argon was used as a carrier gas and a photocatalytic hydrogen production experiment was carried out in a condensed water circulation system at 15°C, and each experiment lasted for 3 hours. Under simulated solar illumination conditions, the hydrogen production rate of the photocatalytic material CN-0.3 reached 5.58mmol / g / h, which is about 6.6 times that of pure CN photocatalytic material. Figure 4 shown.
[0034] In order to test the application effect of the photocatalytic material CN-0.3 in water pollution treatment, a degradation experiment of dye pollutants was carried out. This test intends to use a 500W xenon lamp as a light source to simulate visible light (λ>420nm) to study the degradation effect of CN and the photocatalytic material CN-0.3 prepared in Comparative Example 2 on RhB (as well as TC and CIP) at room temperature. Take RhB as an example. During the experiment, 30mg CN and 30mg photocatalytic material CN-0.3 were respectively added to 50mL of RhB solution with an initial concentration of 10mg / L, and a stirring bar was placed to make the photocatalytic material evenly dispersed in the RhB solution.
[0035] Before the photocatalytic experiment, the photocatalytic material was stirred in the dark for 1 h to reach adsorption-desorption equilibrium. Then the xenon lamp was turned on, 5 mL of the photocatalytic degradation solution was taken every 20 min, and the solution was centrifuged twice at 10,000 rpm to remove the residual photocatalytic material in the solution. Finally, the spectrophotometer (λ max =554) to measure the concentration change of RhB in the solution. Using the formula k = (C0-C t ) / C0 to calculate the photodegradation rate, where C0 and C t They represent the concentration of RhB solution at the initial time and time t respectively. The experimental results show that the photocatalytic reaction rate of the photocatalytic material CN-0.3 is about 2.75 times higher than that of pure CN. Figure 3 As shown, the degradation efficiency of CN sample for RhB is very low, only 36%, while the degradation efficiency of CN-0.3 sample for RhB is as high as 99%. In addition, the photocatalytic degradation experiment of tetracycline (TC) and ciprofloxacin (CIP) by photocatalytic material CN-0.3 also showed a higher degradation rate, 72% of TC and 57% of CIP antibiotics, respectively.
[0036] In order to verify the stability of the photocatalytic performance of the photocatalytic material CN-0.3, five hydrogen production cycle experiments were carried out. The experimental results show that the photocatalytic material CN-0.3 still maintains high photocatalytic activity after five cycles, showing good cycle stability. Figure 5 shown.
[0037] Example 2
[0038] The preparation method of Example 2 is the same as that of Example 1, except that in step (1), the amount of tungsten hexachloride added is 0.1 g, and the photocatalytic material CN-0.1 is obtained. The product testing part (photocatalytic hydrogen production experiment under visible light) is the same as that of Example 1.
[0039] Example 3
[0040] The preparation method of Example 3 is the same as that of Example 1, except that in step (1), the amount of tungsten hexachloride added is 0.2 g, and the photocatalytic material CN-0.2 is obtained. The product testing part (photocatalytic hydrogen production experiment under visible light) is the same as that of Example 1.
[0041] Example 4
[0042] The preparation method of Example 4 is the same as that of Example 1, except that in step (1), the amount of tungsten hexachloride added is 0.5 g, and the photocatalytic material CN-0.5 is obtained. The product testing part (photocatalytic hydrogen production experiment under visible light) is the same as that of Example 1.
[0043] Example 5
[0044] The preparation method of Example 5 is the same as that of Example 1, except that in step (3), the calcination temperature is 500° C. The product testing part (photocatalytic hydrogen production experiment under visible light) is the same as that of Example 1.
[0045] Example 6
[0046] The preparation method of Example 6 is the same as that of Example 1, except that in step (3), the calcination temperature is 550° C. The product testing part (photocatalytic hydrogen production experiment under visible light) is the same as that of Example 1.
[0047] Example 7
[0048] The preparation method of Example 7 is the same as that of Example 1, except that in step (3), the temperature is raised to 520° C. at a heating rate of 1° C. / min in a resistance furnace and calcined for 3 hours. The product testing part (photocatalytic hydrogen production experiment under visible light) is the same as that of Example 1.
[0049] Example 8
[0050] The preparation method of Example 7 is the same as that of Example 1, except that in step (3), the temperature is raised to 520°C at a heating rate of 10°C / min in a resistance furnace and calcined for 3 hours. The product testing part (photocatalytic hydrogen production experiment under visible light) is the same as that of Example 1.
[0051] pass Figure 4 , 6 It can be seen that the hydrogen generation rate of the photocatalytic material CN-0.3 is significantly higher than that of Examples 2 to 8. This indicates that changes in the mixing ratio of the calcined precursors, calcination temperature, time, and calcination heating rate will affect the final morphology of the product, thereby affecting its final photocatalytic performance.
[0052] Comparative Example 1
[0053] Tungsten trioxide alone
[0054] 5.0 g of tungsten hexachloride was placed in 50 mL of deionized water and stirred for 0.5 h, filtered, and washed with deionized water. The filtered solid was dried to remove the moisture therein; then calcined at a high temperature (about 520° C.); dehydrated and decomposed at a high temperature to generate tungsten trioxide; the calcined product was washed three times with ethanol and deionized water, centrifuged, and dried, and recorded as DB1. The test part (photocatalytic hydrogen production experiment under visible light) was the same as Example 1.
[0055] Comparative Example 2
[0056] Carbon nitride alone
[0057] 10.0 g of melamine was placed in a sealed autoclave for a high temperature and high pressure reaction at 500° C. to obtain CN, which was recorded as DB2. The test part (photocatalytic hydrogen production experiment under visible light) was the same as Example 1.
[0058] Comparative Example 3
[0059] A method for preparing a WO3 / CN composite photocatalytic material comprises the following steps:
[0060] (1) Add 10.0 g of thiourea to 20 mL of anhydrous ethanol and stir at room temperature. Then weigh 0.3 g of WCl6 and add it to the thiourea solution. Continue stirring at room temperature to fully mix the reaction materials.
[0061] (2) placing the mixed solution of step (1) in an ultrasonic instrument for ultrasonic treatment for 0.5 hours to form a uniform suspension; the low surface tension of ethanol causes the solid to settle at the bottom of the beaker, taking out the solid mixture at the bottom and placing it in a 60° C. oven for drying for 6 hours;
[0062] (3) The solid mixture obtained in step (2) was fully ground into powder, and then the mixture was placed in an 800W microwave for calcination; after the calcination was completed, it was naturally cooled to room temperature; the powder was washed with anhydrous ethanol and distilled water, and then dried at 60°C to obtain a photocatalytic material, which was recorded as DB3. The test part (photocatalytic hydrogen production experiment under visible light) was the same as Example 1
[0063] Comparative Example 4
[0064] A method for preparing a WO3 / CN composite photocatalytic material comprises the following steps:
[0065] (1) Add 10.0 g of urea to 20 mL of anhydrous ethanol and stir at room temperature. Then weigh 0.3 g of WCl6 and add it to the above thiourea solution. Continue stirring at room temperature to fully mix the reaction materials.
[0066] (2) placing the mixed solution of step (1) in an ultrasonic instrument for ultrasonic treatment for 0.5 hours to form a uniform suspension; the low surface tension of ethanol causes the solid to settle at the bottom of the beaker, taking out the solid mixture at the bottom and placing it in a 60° C. oven for drying for 6 hours;
[0067] (3) The solid mixture obtained in step (2) was fully ground into powder and placed in a 50 mL crucible; then, the temperature was raised to 520° C. at a heating rate of 5° C. / min in a resistance furnace and calcined for 3 hours; after calcination, the mixture was naturally cooled to room temperature; the powder was washed with anhydrous ethanol and distilled water, and then dried at 60° C. to obtain a photocatalytic material, which was recorded as DB4. The test part (photocatalytic hydrogen production experiment under visible light) was the same as Example 1.
[0068] The experimental results are as follows Figure 7 As shown, the experimental results show that the hydrogen generation rate of the photocatalytic material CN-0.3 is significantly higher than that of the photocatalytic materials of comparative examples 1 to 4.
[0069] from Figure 8 It can be seen that CN-0.3 presents needle-like WO3 covering the CN nanosheets. This interfacial contact between CN and WO3 is conducive to the transfer and separation of photoexcited carriers during photocatalysis. HRTEM images confirm that there are loose needle-like WO3 nanorods on the thin CN nanosheets, and the WO3 nanorods are tightly bound to CN, indicating the successful preparation of CN / WO3 composite materials. Figure 8 A lattice with d = 0.374 nm was observed in (d), which may belong to the (020) crystal plane of WO3.
Claims
1. A WO3 / CN composite photocatalytic material based on in-situ coupling, characterized in that: It includes CN nanosheets and WO3 nanorods in situ grown on the CN nanosheets.
2. The method for preparing the WO3 / CN composite photocatalytic material according to claim 1, characterized in that: The steps include: (1) dispersing thiourea in a solvent to obtain a thiourea solution; then adding WCl6 thereto, and continuously stirring at room temperature to mix the materials uniformly; (2) subjecting the mixed material of step (1) to ultrasonic treatment to form a uniform suspension; after solid-liquid separation, drying the obtained solid; (3) After drying, calcination is performed to obtain a WO3 / CN composite photocatalytic material.
3. The preparation method according to claim 2, characterized in that: In step (1), the solvent is anhydrous ethanol.
4. The preparation method according to claim 2, characterized in that: In step (1), the mass ratio of WCl6 to thiourea added is 10:0.1-0.
5.
5. The preparation method according to claim 2, characterized in that: In step (1), the concentration of thiourea in the thiourea solution is 50-60 g / L.
6. The preparation method according to claim 2, characterized in that: In step (2), the ultrasonic treatment time is not less than 0.5 h.
7. The preparation method according to claim 2, characterized in that: In step (2), the drying temperature is 60-70° C. and the drying time is 6-8 hours.
8. The preparation method according to claim 2, characterized in that: In step (3), the calcination temperature is 500-550° C., the calcination time is 2.5-3 h, and the heating rate is 2-10° C. / min.
9. The preparation method according to claim 2, characterized in that: In step (3), after calcination, the product is naturally cooled to room temperature, then washed with anhydrous ethanol and distilled water, and then dried at 60-70°C.